Optimisation of liquorice extract microencapsulation and bioaccessibility of its bioactives - Ozcan, F. S.; Ozcan, N.; Ozkan, K.; Sagdic, O. (AKADEMIAI KIADO ZRT, 2022)
In this work, functional liquorice powder beverage (FLPB) with standardised glycyrrhizin (GL), glycyr-rhetinic acid (GA), carbenoxolone (CBX), and liquiritin (LQ) contents, was produced by encapsulating Glycyrrhiza glabra extract with maltodextrin (MD) by spray drying. Encapsulation parameters of the FLPB were optimised as MD:GL 3.4:1, inlet temperature: 149 8C, and air flow: 8.9 L min -1. GL, GA, LQ, CBX, and yield in powdered beverage produced using these optimised parameters were 6.8 g L-1, 81.1 mg L-1, 24.7 mg L-1, 0.79 g L-1, and 30.95%, respectively. Moreover, the effect of the encapsulation on the bio-accessibility of GL, GA, CBX, and LQ bioactives in G. glabra was evaluated. According to the obtained results, FLPB exhibited a higher bioaccessibility index for GL, GA, CBX, and LQ compared to the aqueous extract.
Keywords: bioactive compounds; in vitro gastrointestinal digestion; liquorice; microencapsulation; optimisation; IN-VITRO; Food Science & Technology; Nutrition & Dietetics